Cytoplasmic Localization of WT1 and Decrease of miRNA-16-1 in Nephrotic Syndrome - Zapata Benavides, Pablo; Arellano Rodríguez, Mariela; Bollain y Goytia de la Rosa, Juan José; Franco Molina, Moisés Armides; Rangel Ochoa, Gloria Azucena; Avalos Díaz, Esperanza; Herrera Esparza, Rafael; Rodríguez Padilla, María Cristina (2017)
Nephrotic syndrome (NS) is a glomerular disease that is defined by the leakage of protein into the urine and is associated with hypoalbuminemia, hyperlipidemia, and edema. Steroid-resistant NS (SRNS) patients do not respond to treatment with corticosteroids and show decreased Wilms tumor 1 (WT1) expression in podocytes. Downregulation of WT1 has been shown to beaffectedbycertainmicroRNAs(miRNAs).Twenty-onepatientswithidiopathicNS(68.75%wereSSNSand31.25%SRNS)and 10healthycontrolswereenrolledinthestudy.PodocytenumberandWT1locationweredeterminedbyimmunofluorescence,and the serum levels of miR-15a, miR-16-1, and miR-193a were quantified by RT-qPCR. Low expression and delocalization of WT1 proteinfromthenucleustothecytoplasmwerefoundinkidneybiopsiesofpatientswithSRNSandbothnuclearandcytoplasmic localization were found in steroid-sensitive NS (SSNS) patients. In sera from NS patients, low expression levels of miR-15a and miR-16-1 were found compared with healthy controls, but only the miR-16-1 expression levels showed statistically significant decrease (